Enhancing constraints and precision studies for a deeper understanding of the universe using CMB and 21cm maps - Mokeddem, Rahima (2023)
This thesis focuses on enhancing constraints and precision studies to deepen our understanding of the universe. By improving measurements and testing methods, we aim to achieve higher-resolution simulations and more precise results. The thesis specifically addresses the lensing amplitude parameter, investigating its accuracy and quantifying any discrepancies. Additionally, we explore the generation of 21cm mocks in different cosmologies, using the remapping technique to obtain reliable results. The findings of this thesis have the potential to revolutionize our understanding of large-scale structures, the cosmic microwave background, and the early and late stages of the universe by precisely estimating the lensing amplitude AL and by introducing for the first time 21cm mocks in three different cosmologies, that were obtained in a very timely mannered way starting from one dark matter halo catalogue.